Community Energy Networks With Storage Modeling Frameworks for Distributed Generation - Khalilpour, Kaveh Rajab; Vassallo, Anthony (Green Energy and Technology, 2016)
This book addresses the problem of building an optimal community energy network in a decentralized distributed energy context. The book introduces a few novel modeling frameworks to assist a single customer or a community of multiple end-user customers in building their optimal electricity system/network and operating their own local energy system. The content of the book is suitable for students, academics and industrial practitioners studying or working in the area of energy management and smart grid energy networks.